Security and Political Discourse : How Does the Naming of Challenges as a Security Issue Determine Political Practice? - Polko, Paulina, (Social Sciences E-Books Online, Collection 2026., 2026)
Based on a review of conceptual and empirical work on security theory, including Securitization Theory (ST), Riskification Theory (RT), and Just Securitization Theory (JST), the analysis of securitization processes in Polish political discourse and their impact on political practice is presented. Paulina Polko proposes a theoretical and practical approach that allows readers to understand why and how selected challenges (risk and threats) are presented as existential threats become security issues, which leads to the acceptance of the use of extraordinary measures to implement practical solutions to fight or manage this challenges, risks, and threats.